EFFECT ON CASH AND DUE FROM WORKING CAPITAL (A case study in Yogyakarta Regional Office Pawnshop from years 2002-2006) - Kikuncoro, Kikuncoro; Kahu Lantum, MS, Drs. Alex (Management, 2010)
Cash and receivables are elements lancar.Aktiva current assets is part of working capital, which also affected the working capital turnover. Cash is the most liquid assets used to finance the company´s operations, while accounts receivable are receivables from buyers or customers due to the sale of goods or services on credit.Public Company (Perum) Pengadaian are credit institutions that provide service assistance in the form of borrowing money with a pledge to the public in general. The number of customers from year to year increase, it is proved that the existence pengadaian really needed by society. Working capital according to the qualitative concept is part of the current assets that can really be used to finance the company´s operations without disrupting likiuditasnya, namely that an excess of current assets over liabilities smooth. The existence of a positive and significant influence in a positive cash turnover and dominant towards the working capital turnover, caused by the cash position is very important information about cash receipts and the financing of an enterprise during a certain period. The higher the company´s cash position, the better the performance of companies in menghasilan company funds. With adnaya cash flow in and out then the resulting change in the amount of funds in cash. More and more funds in the cash working capital that can be used too much, because with the amount of funds that much, given too much credit. The partial rotation of doubtful variables also proved to be positively significant effect on the working capital turnover. This means the higher the velocity of receivables will not affect the large-size company´s working capital turnover. keyword: company,capital,working